2013
DOI: 10.1213/ane.0b013e3182a44d5d
|View full text |Cite
|
Sign up to set email alerts
|

The Cost of Resident Scholarly Activity and Its Effect on Resident Clinical Experience

Abstract: Residents' scholarly activities require significant departmental financial support. Residents who elected to spend months conducting research completed significantly more scholarly projects but experienced fewer clinical cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 13 publications
1
11
1
Order By: Relevance
“…In other words, our findings would suggest that research does not detract from clinical training, which is the main goal of residency training [ 25 , 38 , 39 ]. These findings support a study of residents who, despite logging fewer clinical cases than their colleagues who did not do research, performed better on oral examinations at graduation [ 23 ]. Additionally, these findings underscore a previously-untested assumption that providing education in research during residency training likely improves residents’ skills across all of the ACGME core competencies [ 40 ].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In other words, our findings would suggest that research does not detract from clinical training, which is the main goal of residency training [ 25 , 38 , 39 ]. These findings support a study of residents who, despite logging fewer clinical cases than their colleagues who did not do research, performed better on oral examinations at graduation [ 23 ]. Additionally, these findings underscore a previously-untested assumption that providing education in research during residency training likely improves residents’ skills across all of the ACGME core competencies [ 40 ].…”
Section: Discussionsupporting
confidence: 83%
“…Another study revealed that residents with research experience are more likely to pursue academic careers [ 9 ]. One study demonstrated a correlation between research experience and clinical achievement during residency [ 23 ]. However, the variables in that study were research elective and performance on an oral examination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature suggests that early and appropriate exposure appear as central tenets in inspiring interest in research among residents. 20 While allocating research time in residency will come at the expense of resource provisions and reduced clinical exposure, 21 the benefits are suggested by the results of our logistic regression model, which show that resident research activity is associated with the desire to pursue research after graduation.…”
Section: Future Practice Locationmentioning
confidence: 90%
“…Training programme directors and department chairs/vice chairs must explicitly acknowledge that promoting and implementing an active research and scholarship culture during residency is resource-intensive. Schott et al [ 21 ] have recently shown that residents’ dedicated research electives and tracks required significant departmental financial support. Moreover, residents who elected to spend dedicated months conducting research did complete significantly more scholarly projects than their peers but experienced fewer clinical cases, which may impact the accomplishment of other clinical competencies [ 21 ].…”
mentioning
confidence: 99%